La responsabilité professionnelle au cours des cinquante dernières années - Bergeron, Lucien (Assurances, 1982)
For many years one heard very little tell of professional liability claims in Canada. In his article, Mr. Bergeron traces development in this field over the past fifty years and points out with reason that individuals in the United States, and to a lesser degree in Canada, have, over the last decade, tended increasingly to rashly affirm their real or imagined rights. The author examines the ramifications of this issue as they pertain to the insurance industry.